Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21203/rs.2.9666/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking Variant Identification Tools for Plant Diversity Discovery

Abstract: Background The ability to accurately and comprehensively identify genomic variations is critical for plant studies utilizing high-throughput sequencing. Most bioinformatics tools for processing next-generation sequencing data were originally developed and tested in human studies, raising questions as to their efficacy for plant research. A detailed evaluation of the entire variant calling pipeline, including alignment, variant calling, variant filtering, and imputation was performed on different programs usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…In terms of sensitivity, GATK in combination with CLC-mapper, Novoalign and BWA-MEM yielded the best and most consistent results across all evaluated data sets. These results are in line with a recent study showing that GATK often outperformed SAMtools in terms of sensitivity, precision, and called raw InDels 44 . A high sensitivity is essential when a high number of true positives variations accelerates the power of the analyses, e.g.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In terms of sensitivity, GATK in combination with CLC-mapper, Novoalign and BWA-MEM yielded the best and most consistent results across all evaluated data sets. These results are in line with a recent study showing that GATK often outperformed SAMtools in terms of sensitivity, precision, and called raw InDels 44 . A high sensitivity is essential when a high number of true positives variations accelerates the power of the analyses, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, we performed a benchmarking study to provide comparable data showing the performance of combinations of frequently applied mappers and variant callers (variant calling pipelines) on plant data sets. A previous report 44 is extended by providing data about the performance of additional tools both for the mapping and variant calling step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They, too showed that BWA-MEM outperformed other aligners in mapping percentage and accuracy. Alike, for variant calling Wu et al (2019) also observed the increase in the number of SNPs when using GATK HaplotypeCaller in comparison to the SAMtools. They also showed that variant calling and filtering using GATK HaplotypeCaller outperformed SAMtools in terms of precision and recalling of variants in highly diverse samples.…”
Section: Evaluation Of Mapping and Variant Calling Pipelinementioning
confidence: 91%
“…Recently Wu et al (2019) compared three sequence aligners, BWA-MEM, Bowtie2 and SOAP2, and two variant callers GATK HaplotypeCaller and SAMtools mpileup for benchmarking tools for plant diversity discovery using domesticated, wild-relatives, and simulated genomic datasets of tomato. They, too showed that BWA-MEM outperformed other aligners in mapping percentage and accuracy.…”
Section: Evaluation Of Mapping and Variant Calling Pipelinementioning
confidence: 99%